Protein kinase D1 induces G1‐phase cell‐cycle arrest independent of Checkpoint kinases by phosphorylating Cell Division Cycle Phosphatase 25. Issue 9 (8th April 2019) - Nickkholgh, Bita; Sittadjody, Sivanandane; Ordonez, Karina; Rothberg, Michael Bryan; Balaji, K. C.
Abstract: Protein Kinase D1 (PrKD1) functions as a tumor and metastasis suppressor in several human cancers by influencing cell‐cycle progression. However, the exact mechanism of cell‐cycle regulation by PrKD1 is unclear. Overexpression and ectopic expression of PrKD1 induces G1 arrest in cancer cell lines. Because checkpoint kinases (CHEKs) are known to play a role in progression through the G1 phase, we downregulated CHEK1, which did not overcome the G1 arrest induced by PrKD1. Using in vitro phosphorylation and Western blot assays, we showed that PrKD1 phosphorylates all CDC25 isoforms (known substrates of CHEK kinases), independent from CHEK kinases, suggesting that direct phosphorylation of CDC25 by PrKD1 may be an alternate mechanism of G1 arrest. The study has identified a molecular mechanism for the influence of PrKD1 in cell‐cycle progression.